WOOLWICH MASSAGE COUNSELING TO FACILITATE BREASTFEEDING FOR POSTPARTUM MOTHERS AT TPMB BRAHMANITA PERBON TUBAN REGENCY - qiftiyah, mariyatul; eka wijayanti, erna; Nurcholila (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2025)
Background: The Woolwich massage technique can help stimulate the hypothalamus to increase the hormones prolactin and oxytocin by providing a relaxing sensation. This happens because gentle touch and massage movements can stimulate the nervous system, which in turn can stimulate the release of relaxation hormones. This can help calm the mind and body as a whole so that it can help postpartum mothers to be able to provide exclusive breastfeeding. Exclusive breastfeeding can help build antibodies in babies so they are protected from various diseases such as diarrhea and pneumonia. Increasing breastfeeding rates internationally has the potential to potentially save the lives of more than 820,000 children under five and can slow the increase of 20,000 cases of breast cancer each year in women. Method: This extension activity applies an educational and preventive approach. By providing clear information about the Woolwich massage technique, previously given a questionnaire on postpartum mothers' knowledge of the Woolwich massage technique and evaluated after counseling. Results: Education on the Woolwich massage technique was successful in increasing postpartum mothers' understanding of the purpose, benefits, Wolwich massage technique and the timing of the Woolwich massage technique for postpartum mothers. The active participation of postpartum mothers shows a high level of involvement. conclusion, this activity not only provides knowledge, but also increases postpartum mothers' awareness of the relationship between the Woolwich massage technique and the flow of breast milk. Background: The Woolwich massage technique can help stimulate the hypothalamus to increase the hormones prolactin and oxytocin by providing a relaxing sensation. This happens because gentle touch and massage movements can stimulate the nervous system, which in turn can stimulate the release of relaxation hormones. This can help calm the mind and body as a whole so that it can help postpartum mothers to be able to provide exclusive breastfeeding. Exclusive breastfeeding can help build antibodies in babies so they are protected from various diseases such as diarrhea and pneumonia. Increasing breastfeeding rates internationally has the potential to potentially save the lives of more than 820,000 children under five and can slow the increase of 20,000 cases of breast cancer each year in women. Method: This extension activity applies an educational and preventive approach. By providing clear information about the Woolwich massage technique, previously given a questionnaire on postpartum mothers' knowledge of the Woolwich massage technique and evaluated after counseling. Results: Education on the Woolwich massage technique was successful in increasing postpartum mothers' understanding of the purpose, benefits, Wolwich massage technique and the timing of the Woolwich massage technique for postpartum mothers. The active participation of postpartum mothers shows a high level of involvement. conclusion, this activity not only provides knowledge, but also increases postpartum mothers' awareness of the relationship between the Woolwich massage technique and the flow of breast milk.